Tracheal Intubation in Emergency Departments in China: A National Cross-Sectional Survey - Dai, Yili; Walline, Joseph Harold; Yu, Heng; Zhu, Huadong; Xu, Jun; Yu, Xuezhong (Frontiers in Medicine, 2022)
Background Tracheal intubation is a necessary but risky procedure performed in emergency departments (EDs) around the world. Relatively high morbidity has been encountered in Chinese EDs, which has raised concerns about peri-intubation ED management. This study aimed to investigate intubation procedures and identify any areas for improvement in Chinese EDs. Methods This was a questionnaire-based survey lasting 1 month (March 2021) in 41 tertiary-care hospital EDs in mainland China. The primary outcome was complications associated with intubation. Secondary outcomes were the first-pass success rate and blood pressure variations during intubation. Univariate and binary logistic regression analyses were used to find possible risk factors for first-pass intubation failure. Results In total, 1,020 replies were analyzed out of 1,080 surveys submitted (94.4% response rate). Most patients were elderly men with severe medical conditions like cardiac arrest (24.8%). In total, 97.2% of patients were given preoxygenation, and 48.1% received some form of pretreatment. Induction drugs (e.g., etomidate and ketamine) were less often used: 39.9% of intubations used sedatives, 5.5% used analgesics, and only 5.3% used muscle relaxants. The overall first-pass intubation success rate was 85.7% and was accompanied by a 19.8% adverse event rate. A marked decrease in blood pressure after intubation was also identified. Conclusion This survey found an 85.7% tracheal intubation first-pass success rate (which is relatively high compared to other countries) and a 19.8% adverse event rate (which is also relatively high). Given the very low rate of using induction medications (5.3% used muscle relaxants), future education should focus on induction drugs and traditional intubation techniques.